OTHR-04. Gynecological Malignancies With Metastasis To The Central Nervous System: A Case Series and Systematic Review of the Literature. (9th August 2021) - Sajjad, Azeem; Adesina, Adeleso; Halkiadakis, Penelope; Murphy, Kelsey; Mulligan, Kathleen; Labak, Collin; Wijesekera, Olindi; Hodges, Tiffany
Abstract: Introduction: Gynecologic malignancies are an increasingly common proportion of central nervous system metastatic disease. As genetic sequencing technology improves and becomes more accessible, mutations associated with CNS metastasis are easier to elucidate. The aims of this case series and systematic literature review are to describe the patient population with CNS metastatic disease from a gynecologic primary, and to investigate why the proportion of CNS metastasis from gynecologic malignancies is increasing. Ultimately, we hope to improve understanding of this subset of metastatic CNS malignancies and improve management strategies. Methods: A literature review of articles describing patients from 1990–2020 who were diagnosed with CNS metastasis from a known gynecologic primary malignancy was performed. Demographics, cancer type, mutation characteristics, management for metastatic disease, progression free survival, number of CNS metastases, and location of metastatic disease were assessed. Inclusion criteria were age>18 years, diagnosis of primary ovarian, uterine, or cervical cancer with confirmed metastatic disease to the CNS, including brain parenchyma, leptomeninges, or intradural spinal cord or dural metastases. Exclusion criteria included pediatric population and bony metastases (e.g., bony spine metastases without evidence of meningeal/parenchymal invasion). Results: Our review showed that patients with gynecological metastasis to the CNS generally have worse outcomes regarding overall survival, progression free survival, and quality of life than patients without CNS metastasis. Discussion: Our results infer that the reported increase in incidence of CNS metastasis from gynecologic malignancies is a reflection of improvement of detection given advances in technology, improved patient follow up, and increased overall survival of patients with gynecologic malignancies. Further characterization of mutations from gynecologic malignancies associated with brain metastasis could result in development of more treatment options for patients in the future and help determine factors that contribute to developing metastasis to the CNS of various degrees, thus, potentially inform treatment strategies.